Correction: Facile one-pot synthesis of silver nanoparticles encapsulated in natural polymeric urushiol for marine antifouling. Issue 41 (25th June 2020) - Zheng, Lu; Lin, Yucai; Wang, Donghui; Chen, Jipeng; Yang, Ke; Zheng, Binbin; Bai, Weibin; Jian, Rongkun; Xu, Yanlian
Abstract : Correction for 'Facile one-pot synthesis of silver nanoparticles encapsulated in natural polymeric urushiol for marine antifouling' by Lu Zheng et al., RSC Adv., 2020, 10, 13936–13943, DOI: ; 10.1039/D0RA02205E .